RISK MANAGEMENT PRACTICES OF SELECTED ISLAMIC BANKS IN MALAYSIA - Noraini Mohd Ariffin; Salina Kassim (Aceh International Journal of Social Science, 2014)
Abstract: This study explores the risk management practices of major Islamic banks in Malaysia with the objective of having deeper understanding of the practices and identifying ways for further improvements. Various aspects of risk management practices are assessed through survey questionnaires, particularly those relevant and specific to the case of the Islamic banks. The study finds that the Islamic banks adopt good risk management practices with few areas of improvements include the use of computerised support systems and more sophisticated approaches to measure risks and the use of Shari’ah compliance techniques to mitigate risks. By assessing their current risk management practices, the study hopes to contribute in terms of recommending strategies to strengthen the risk management practices of the Islamic banks so as to increase the overall competitiveness in the Islamic banking industry. Keywords: risk management; Islamic banks; competitiveness